2012
DOI: 10.1371/journal.pone.0042218
|View full text |Cite
|
Sign up to set email alerts
|

Tubulin Acetylation Alone Does Not Affect Kinesin-1 Velocity and Run Length In Vitro

Abstract: Kinesin-1 plays a major role in anterograde transport of intracellular cargo along microtubules. Currently, there is an ongoing debate of whether α-tubulin K40 acetylation directly enhances the velocity of kinesin-1 and its affinity to the microtubule track. We compared motor motility on microtubules reconstituted from acetylated and deacetylated tubulin. For both, single- and multi-motor in vitro motility assays, we demonstrate that tubulin acetylation alone does not affect kinesin-1 velocity and run length.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
94
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(100 citation statements)
references
References 28 publications
(36 reference statements)
4
94
1
1
Order By: Relevance
“…Acetylated microtubules are generally thought to be more stable than unmodified microtubules, but no direct evidence has shown that acetylation modification of microtubules directly influences tubulin polymerization or depolymerization kinetics in vitro (18). In addition, no clear differences in microtubule structure or tubulin conformation have been found between electron cryomicroscopy reconstructions of maximally deacetylated or acetylated microtubules (19), and the levels at which kinesin-1 binds to acetylated microtubules and deacetylated microtubules are similar (20,21). These findings require further investigation into the mechanism by which acetylation of ␣-tubulin enhances the fusion of IBs of HPIV3 via interaction with the N-P complex.…”
Section: Discussionmentioning
confidence: 99%
“…Acetylated microtubules are generally thought to be more stable than unmodified microtubules, but no direct evidence has shown that acetylation modification of microtubules directly influences tubulin polymerization or depolymerization kinetics in vitro (18). In addition, no clear differences in microtubule structure or tubulin conformation have been found between electron cryomicroscopy reconstructions of maximally deacetylated or acetylated microtubules (19), and the levels at which kinesin-1 binds to acetylated microtubules and deacetylated microtubules are similar (20,21). These findings require further investigation into the mechanism by which acetylation of ␣-tubulin enhances the fusion of IBs of HPIV3 via interaction with the N-P complex.…”
Section: Discussionmentioning
confidence: 99%
“…However, a direct regulation of kinesin-1 motility by K40 acetylation of tubulin has not been confirmed in vitro (Kaul et al, 2014;Walter et al, 2012), suggesting that other mechanisms contribute to the transport phenotype observed in cells.…”
Section: Molecular Mechanisms Controlled By Tubulin Ptmsmentioning
confidence: 97%
“…A consecutive change in MT conformation might therefore enhance motor recruitment to MTs (Dompierre et al, 2007;Hammond et al, 2009;Reed et al, 2006). Conversely, the role of tubulin acetylation upon molecular motor recruitment and function has been questioned in motility assays using tubulin acetylated in vitro (Soppina et al, 2012;Walter et al, 2012). These studies proposed that the recruitment of kinesin-1 to acetylated MTs and its velocity were not affected, but other tubulin modifications (de-tyrosination and polyglutamylation) could have masked the effect of acetylation.…”
Section: Autophagy and Microtubules 1075mentioning
confidence: 99%